Status of the Eastern Imperial Eagle in Hungary Between 2019 and 2023 - Márton Horváth; Tibor Juhász; Imre Fatér; Gábor Deák; Márton Árvay; Szilvia Pásztory-Kovács (Пернатые хищники и их охрана)
The Hungarian population of the Eastern Imperial Eagle (Aquila heliaca) is closely monitored by MME BirdLife Hungary and the ranger service of the Hungarian national park directorates since 1980. The population is slowly, but continuously increasing during the last four decades and the average population growth rate is 11% and the number of estimated nesting population has increased from 230–240 pairs (2018) to 400–450 (2023).